Mapping and visualization of global research progress on deubiquitinases in ovarian cancer: a bibliometric analysis - Qiu, Fang; Li, Yuntong; Zhou, Lile; Wu, Yingli; Wu, Yunzhao; Fan, Zhilei; Wang, Yingying; Qin, Dongjun; Li, Chaoqun (Frontiers in Pharmacology, 2024)
Background: Ovarian cancer is a highly aggressive malignancy with limited therapeutic options and a poor prognosis. Deubiquitinating enzymes (DUBs) have emerged as critical regulators of protein ubiquitination and proteasomal degradation, influencing various cellular processes relevant to cancer pathogenesis. This study mapped and visualized the research progress between ovarian cancer and DUBs using bibliometrics, and summarized the expression patterns and biological roles of DUBs in ovarian cancer. Methods: Studies related to DUBs in ovarian cancer were extracted from the Web of Science Core Collection (WoSCC) database. VOSviewer 1.6.20, CiteSpace 6.3.R1, and R4.3.3 were used for bibliometric analysis and visualization. Results: This study included 243 articles for analysis. The number of publications on DUBs in ovarian cancer has gradually increased each year. China, the United States and the United Kingdom are at the center of this field of research. The Johns Hopkins University, Genentech, and Roche Holding are the main research institutions. David Komander, Zhihua Liu and Richard Roden are top authors in this field. The top five journals with the largest publication volumes in this field are Biochemical and Biophysical Research Communications, Journal of Biological Chemistry, PLoSOne, Nature Communications and Oncotarget. Keywords burst analysis identified five research areas: "deubiquitinating enzyme," "expression," "activation," "degradation," and "ubiquitin." In addition, we summarized the expression profiles and biological roles of DUBs in ovarian cancer, highlighting their roles in tumor initiation, growth, chemoresistance and metastasis.This study provides an overview of the research progress on DUBs in ovarian cancer over the last three decades. It offers insight into the most cited papers and authors, core journals and identified new trends.